Flipped Classroom Strategy in Improving Achievement and Motivation of Madrasah Tsanawiyah Students - Mahmud Wantu, Hasyim; Emer, Souza; Lisnawaty, Sri Dewi; Badruzzaman, Badruzzaman; Dewi, Risma Kartika (World Psychology, 2024)
Motivation to learn is very important for every student at school, especially at the Madrasah Tsanawiyah level. In addition, the support for a student at school is his achievement. This study aims to describe the flipped classroom strategy in Madrasah Tsanawiyah. In this study, researchers used quantitative methods using a survey model, conducted by online and in-depth interviews. The research subjects in this case are educators and students who are in school in Flipped classroom learning. The method that the researcher used to collect data was interview. This study found that the use of Flipped classroom can make learners more active and independent in understanding the learning material provided. This can be proven by the habit of students who are getting used to studying at home. This flipped classroom allows students to be more inclined to develop themselves to know this learning. The limitation of this study is that researchers have not developed a perfect flipped classroom to measure the level of teacher proficiency. Therefore, the next researcher can conduct research that aims to perfect flipped classroom learning.